What is the potential impact of genetic divergence of plastid ribosomal genes between Silene nutans lineages in hybrids? An in silico approach using the 3D structure of the plastid ribosome - Postel, Zoé; Mauri, Théo; Lensink, Marc F.; Touzet, Pascal (Frontiers in Plant Science, 2023)
Subsequently to the integration of cyanobacteria into the eukaryotic cells, many genes were transferred from the plastid to the nucleus. As a result, plastid complexes are encoded both by plastid and nuclear genes. Tight co-adaptation is required between these genes as plastid and nuclear genomes differ in several characteristics, such as mutation rate and inheritance patterns. Among these are complexes from the plastid ribosome, composed of two main subunits: a large and a small one, both composed of nuclear and plastid gene products. This complex has been identified as a potential candidate for sheltering plastid-nuclear incompatibilities in a Caryophyllaceae species: Silene nutans. This species is composed of four genetically differentiated lineages, resulting in hybrid breakdown when conducting inter-lineage crosses. As this complex is composed of numerous interacting plastid-nuclear gene pairs, in the present study we aimed at further eliminating gene pairs unlikely to induce such incompatibilities. We used the previously published 3D structure of the spinach ribosome to further elucidate which of the potential gene pairs identified might result in modification of the plastid-nuclear interactions within this complex. After modeling the impact of the identified mutations on the 3D structure we further focused on one strongly mutated plastid-nuclear gene pair: rps11-rps21. We used the centrality measure of the mutated residue to further understand if the modified interaction and associated modified centrality might be correlated with hybrid breakdown. This study highlights that lineage-specific mutations in essential plastid and nuclear genes might disrupt plastid-nuclear proteins interactions of the plastid ribosome and that reproductive isolation correlates with changes in residue centrality values. Because of this, the plastid ribosome might be involved in hybrid breakdown in this system.